Interfacial Band Bendings in Al Ohmic Contacts to Laser-Irradiated Ga-Face and N-Face n-GaN - Jang, Ho Won; Lee, Sanghan; Ryu, Seong Wook; Son, Jun Ho; Song, Yang Hee; Lee, Jong-Lam (ELECTROCHEMICAL SOC INC, 2009)
We investigate interfacial band bendings in Al ohmic contacts to laser-irradiated Ga-face and N-face n-GaN using synchrotron radiation photoemission spectroscopy. Both samples show increased band bendings after annealing at 300 degrees C, but annealing at 500 degrees C leads to completely opposite band bendings. These two different behaviors with annealing temperature are consistent with electrical properties of the contacts and are well explained by the annihilation of N vacancies at the interface and the formation of polarization-induced sheet charges at AlN/GaN heterointerfaces, respectively.
Keywords: LIGHT-EMITTING-DIODES; METAL CONTACTS; TI/AL CONTACTS